Barthes' Mythologies today readings of contemporary culture - edited by Pete Bennett (London Routledge, 2013)
"No denunciation without its proper instrument of close analysis," Roland Barthes wrote in his preface to Mythologies. There is no more proper instrument of analysis of our contemporary myths than this book―one of the most significant works in French theory, and one that has transformed the way readers and philosophers view the world around them.
Includes bibliographical references and index.
Keywords: Barthes, Roland. Mythologies